2003
DOI: 10.1039/b300360d
|View full text |Cite
|
Sign up to set email alerts
|

Does the DABCO-catalysed reaction of 2-hydroxybenzaldehydes with methyl acrylate follow a Baylis–Hillman pathway?

Abstract: Evidence is presented which supports the intermediacy of dipolar Baylis-Hillman-type adducts in the synthesis of coumarin and chromene derivatives from the reaction of 2-hydroxybenzaldehydes with methyl acrylate in the presence of 1,4-diazabicyclo[2.2.2]octane (DABCO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…It is well known that the reactions of salicylaldehydes with acrylonitrile [27][28][29], alkyl vinyl ketones [30][31][32][33], and nitro alkenes [34][35][36][37][38][39] give 3 -chromenes containing electron-withdrawing substituents at the 3-position. Although these compounds are not found in nature, their derivatives are reported to be useful from industrial and medical points of view [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the reactions of salicylaldehydes with acrylonitrile [27][28][29], alkyl vinyl ketones [30][31][32][33], and nitro alkenes [34][35][36][37][38][39] give 3 -chromenes containing electron-withdrawing substituents at the 3-position. Although these compounds are not found in nature, their derivatives are reported to be useful from industrial and medical points of view [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…2-Acetyl-6-methyl-3,4-dihydro-2H-pyran (11). MVK (0.219 g, 3.13 mmol) was added to zeolite Csβ (0.047 g).…”
Section: -mentioning
confidence: 99%
“…This compound was obtained previously in [5]. Various catalysts have been applied for the synthesis of chromenes and their derivatives, including complexes of palladium and ruthenium [6][7][8], secondary amines [9], cyclic diamines [10][11][12], and zeolites [13]. It is known that the interaction of salicylaldehyde derivatives with various α,β-unsaturated carbonyl compounds in the presence of basic catalysts proceeds as a tandem Michael oxareaction and aldol condensation [10,14] (Scheme 2).…”
mentioning
confidence: 99%
“…14e16 Our interest in benzopyran chemistry has involved research on Baylis-Hillman reactions of 2-hydroxybenzaldehydes with ethyl-or methyl acrylatedreactions which afforded complex mixtures of coumarin and 2H-chromene derivatives (Path I, Scheme 1). 17,18 Cyclisation to form coumarins involves intramolecular acyl substitution by the phenolic hydroxyl group, and it was found that replacement of the ester function (R 1 ¼CO 2 Me/Et) in the activated alkene (2) by electron-withdrawing groups incapable of undergoing acyl substitution (R 1 ¼CN, COMe, SO 2 Ph, SO 3 Ph) resulted in the chemoselective formation of 3-substituted 2H-chromenes (3) via a conjugate-addition elimination pathway (Path II). 19,20 Chemoselective access to coumarins (6), on the other hand, was achieved, initially, using protection strategies (Path III).…”
Section: Introductionmentioning
confidence: 98%